Real-world data of cardio-oncologic interventions for cardiovascular adverse events with oral oncolytics - Karen Abboud; Godsfavour Umoru; Barry Trachtenberg; Veronica Ajewole (Cardio-Oncology, 2024)
Abstract Background Oral cancer therapy-related cardiovascular (CV) toxicity has a wide variety of presentations including arrhythmia, cardiomyopathy, and myocardial infarction, but clinical evidence related to its management is limited. The purpose of this IRB-approved, single-center, retrospective, cohort study was to characterize cardio-oncologic interventions for CV adverse events related to oral oncolytics. Methods The cohort included 67 patients who were admitted to a multi-hospital health system between June 1, 2016 and July 31, 2021, had at least one medical record order of oral oncolytics considered to have cardiotoxic potential, and had an ICD10 code for a cardiotoxic event added to their electronic medical records after initiation of oral oncolytics. Results The majority (97%) had pre-existing cardiovascular disease (CVD) or a CV risk factor. The three most common classes of oral oncolytics were aromatase inhibitors (36%), BCR-ABL inhibitors (16%), and VEGFR inhibitors (13%). New-onset or worsening heart failure (HF) (n = 31), which occurred after a median of 148 days (Interquartile range (IQR) 43–476 days) was the most common cardiotoxic event. The most frequent interventions were pharmacological treatment of the CV adverse event (n = 44) and treatment interruption (n = 18), but guideline-directed medication therapy for HF could be further optimized. Conclusion Pre-existing CVD or CV risk factors predispose oncology patients to CV adverse events. Real-world practice reveals that CV adverse events require temporary interruption of treatment and initiation of pharmacologic treatment. A multidisciplinary, patient-centered approach that includes discussion of risks/benefits of treatment continuation, and initiation of guideline-directed treatment is recommended until high-quality, drug-specific data for monitoring and treatment become available.